2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944693
|View full text |Cite
|
Sign up to set email alerts
|

Novel prediction of anticancer drug chemosensitivity in cancer cell lines: Evidence of moderation by microRNA expressions

Abstract: The objectives of this study are (1) to develop a novel "moderation" model of drug chemosensitivity and (2) to investigate if miRNA expression moderates the relationship between gene expression and drug chemosensitivity, specifically for HSP90 inhibitors applied to human cancer cell lines. A moderation model integrating the interaction between miRNA and gene expressions was developed to examine if miRNA expression affects the strength of the relationship between gene expression and chemosensitivity. Comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Similarly, previous literature has shown that miR-624 is upregulated in ESCC to an extent that is positively correlated with the progression of ESCC [ 10 ]. In addition, miR-624 has been confirmed to function as a potential candidate to regulate the sensitivity to chemotherapy in cancer treatment [ 26 ]. Findings from the current study demonstrated that miR-624 was expressed at a higher level in the drug-resistant ESCC cell line KYSE410 than in the drug-sensitive cell line KYSE150.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous literature has shown that miR-624 is upregulated in ESCC to an extent that is positively correlated with the progression of ESCC [ 10 ]. In addition, miR-624 has been confirmed to function as a potential candidate to regulate the sensitivity to chemotherapy in cancer treatment [ 26 ]. Findings from the current study demonstrated that miR-624 was expressed at a higher level in the drug-resistant ESCC cell line KYSE410 than in the drug-sensitive cell line KYSE150.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated a key role of miR-138 in the progression and metastasis (39) and the development of chemoresistance in cancers of different origins (29;40). We found miR-138 to specifically target K2 and to suppress its expression.…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-miR-519e belongs to the large (>50) miR-515 family coded in a cluster on 19q13.42. It is not a highly validated miRNA gene and is not well recognized as a cancer-related miRNA; however, it was shown to have decreased levels in epithelial ovarian cancer, increased levels in ovarian cancer 93 , and decreased levels upon 17-estradiol (E2) treatment in the MCF-7 breast cancer cell line 94 and was shown in a cell line experiment to influence anticancer drug chemosensitivity 95 .…”
Section: Hsa-mir-519ementioning
confidence: 99%